Portrait of tourism object in Bongan Tabanan Bali village: Cultural studies perspective - NURUDDIN, S.S; ARDIKA, w; KRISTIANTO, Y; MAHAGANGGA, G.A.O; SURYAWAN, I.B; SENDRA, I.M (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The development of tourist villages in Indonesia that rely on culture is quite good. This study looks at the development of these attractions related to the utilization of cultural heritage from the perspective of cultural science theory. The research method used is a descriptive qualitative approach to historical methods and cultural studies. Data search is done by participant observation, documentation and in-depth interviews with stakeholders in the tourist area. As a result, the development of the Bonga Tabanan Tourism Village in Bali relies heavily on cultural heritage. This is following the theory of Pierre Boudieu.